A Study On Congratulating Utterances For The Royal Baby Of Prince William And Chaterine Middleton - Wulandari, Ajeng; , Drs. Agus Wijayanto M.A., Ph.D; , Siti Zurhriah Ariatmi, M. Hum (2014)
This research aims at describing the strategy congratulating utterances, the type of address form and its social function found in congratulating utterances for the Royal Baby of Prince William and Chaterine Middleton. The type of this research is descriptive qualitative research which the writer uses documentation method as the method of collecting data. The data of this research are congratulating utterances. The data sources are social media in internet such as twitter, facebook and online newspaper. In analyzing data, the writer describes of type of address form by referring to the theory of Chaka (1982) and the social function of address from by referring to the theory of Holmes (1992). The result of the research shows that firstly, strategies of congratulating utterance are divided into two categories. They are general pattern (83 data/100, 83%) and idiosyncratic pattern (17 data/100, 17%). Secondly, types of address form are Aristocratic title (24 data/100, 24%), occupational title + Aristocratic title (1 data/100, 1%), title alone (3 data/100, 3%), Aristocratic title + title (3 data/100, 3%), first name (4 data/100, 4%), title + first name (1 data/100, 1%), title first name (3 data/100, 3%), Aristocratic title + title first name (1 data/100, 1%), nickname (4 data/100, 4%), first name + nickname (8 data/100, 8%), title nickname (2 data/100, 2%), title first name + title nickname (1 data/100, 1%), pronoun (5 data/100, 5%), pronoun + Aristocratic (1 data/100, 1%) pronoun + first name (2 data/100, 2%) and does not use address form (37 data/100, 37%). Thirdly, the social functions of address form are to show formality (15 data/100, 15%), to show respect (9 data/100, 9%), to show solidarity (4 data/100, 4%), to show intimacy (9 data/100, 9%), to show formality and respect (3 data/100, 3%), to show respect and solidarity (2 data/100, 2%), to show solidarity and intimacy (10 data/100, 10%) and does not have social function (37 data/100, 37%).